Performance of Two Aman Rice Varieties Using Varying Plant Density in the Northeastern Region Of Bangladesh (Bangladesh Agronomy Journal, 2022)
The experiment was conducted to assess the performance of two popular rice varieties with varying spacing at a farmer's field in Darbost union of Jaintapur Upazila under the Sylhet district of Bangladesh during aman season 2016. Two aman rice varieties (BRRI dhan34 and Binadhan-17), and four levels of plant density (15×10 cm, 20×10 cm, 20×15 cm, and 25×15 cm) were tested in a factorial randomized complete block design (RCBD) with three replications. The results indicated that yield and yield attributes of rice differed significantly due to varieties, spacing, and their interaction. It was recorded that var. Binadhan-17 showed maximum flag leaf length (34.33 cm), maximum number of filled grains m−2 (27855), maximum grain weight m−2 (654.58) contributed to increase grain yield (6.55 t ha−1) in closer spacing (20×10 cm), which ultimately increased grain yield. Therefore, the results of the present study suggested that rice var. Binadhan-17 could be transplanted at 20×10 cm spacing for getting maximum yield (6.55 t ha−1) in northeastern region of Bangladesh.Bangladesh Agron. J. 2021, 24(2): 1-12